PENGARUH PENGENDALIAN INTERNAL DAN EFEKTIVITAS METODE PENDETEKSIAN TERHADAP PENCEGAHAN TINDAKAN KECURANGAN PADA KANTOR INSPEKTORAT PROVINSI SULAWESI SELATAN - Amelia Pusparini; Muhammad Su’un; Musliha Shaleh (Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2023)
This study aims to examine the influence of internal control and the effectiveness of detection methods on fraud prevention within government institutions, praticulary at the Inspectorate Office of South Sulawesi Province. This research employs a quantitative method using a direct field survey approach. The sampling technique used is saturated sampling, as the entire population was taken as respondents. The data were obtained through questionnaires distributed to 36 auditors at the Inspectorate Office of South Sulawesi Province. The data were then analyzed using multiple linear regression. The stages of data analysis include descriptive statistical tests, instrument testing, classical assumption tests, and hypothesis testing. The results of the study show that both internal control and the effectiveness of detection methods have a significant positive influence on fraud prevention. Among the two, the effectiveness of detection methods contributes more substantially to fraud prevention.